Pengaruh Lingkungan Asrama dalam Pembelajaran Bahasa Arab di Pondok Pesantren Syech Ahmad Chatib - Islami, Fikriah; Fadli, Afdhil (Yayasan Lembaga Studi Makwa, 2024)
Syech Ahmad Chatib Islamic Boarding School, which follows the Salafiyah education system, requires all students to reside in dormitories and communicate in Arabic and English daily. Although the institution has only been operational for three years, its graduates are expected to be proficient in multiple languages. This study aims to examine the Arabic language learning system based on routines designed to familiarize students with speaking the language. Using a qualitative approach with a descriptive method, data collection was conducted through observations, interviews, and documentation. The primary focus of this research is to analyze how the environment influences students' use of Arabic, particularly in daily interactions. The findings indicate that the success of Arabic language learning heavily depends on the creation of a supportive linguistic environment. Speaking fluency, as a crucial aspect of language skills, is difficult to achieve without proper environmental arrangements. Therefore, establishing a language-friendly atmosphere should be a shared responsibility among dormitory administrators and school management. Active participation from all elements of the boarding school in fostering a conducive linguistic environment enhances the effectiveness of learning. Several strategies implemented in creating this environment include vocabulary building (mufrodat), displaying Arabic vocabulary in dormitory areas, daily conversations in Arabic, as well as speech and drama activities conducted in Arabic. Consequently, the boarding school environment plays a significant role in improving students' Arabic language proficiency effectively and sustainably.